Gibraltar : Assessment of Financial Sector Supervision and Regulation including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Supervision, and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2007)
This paper presents Gibraltar's assessment of Financial Sector Supervision and Regulation including reports on the Observance of Standards and Codes on banking and insurance supervision. The Financial Services Commission has been assigned significant additional resources and has developed a well-structured approach to the management of its resources that includes a risk-based approach to supervision. The assessment found a high standard of compliance with the Basel Core Principles for banking supervision.